1997
DOI: 10.1007/s001250050660
|View full text |Cite
|
Sign up to set email alerts
|

Defects in insulin signal transduction in liver and muscle of pregnant rats

Abstract: Insulin resistance during pregnancy has been reported both in women and in experimental animals [1][2][3][4][5][6][7], but the mechanism of this resistance remains unclear. In vivo studies have shown that pregnant rats become progressively resistant to insulin after day 16 of gestation [5]. In these animals, the insulin resistance of skeletal muscle has been clearly demonstrated in vitro, while the insulin resistance in vivo in peripheral tissues and liver has been substantiated in studies using the euglycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2
9

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 52 publications
5
31
2
9
Order By: Relevance
“…Taking these data together with our own findings, we postulated that the decrease in insulin sensitivity in group E between days 11 and 16 of treatment could be related to a release of IRS-1 protein from the cytoskeletal scaffold, where it is able to interact with the insulin receptor and pass to the cytosol, where it could be recruited by another hormonal signalling pathway. However, our results on IRS-1 seem not to confirm those of Saad et al (1997), who reported a decrease in the expression of IRS-1 in skeletal muscle during late pregnancy. We consider that these differences could have various explanations.…”
Section: Discussioncontrasting
confidence: 99%
“…Taking these data together with our own findings, we postulated that the decrease in insulin sensitivity in group E between days 11 and 16 of treatment could be related to a release of IRS-1 protein from the cytoskeletal scaffold, where it is able to interact with the insulin receptor and pass to the cytosol, where it could be recruited by another hormonal signalling pathway. However, our results on IRS-1 seem not to confirm those of Saad et al (1997), who reported a decrease in the expression of IRS-1 in skeletal muscle during late pregnancy. We consider that these differences could have various explanations.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with the report of Bezerra et al (2000) who stated that there was a significant reduction in the level of hepatic and muscle IRS-1 tyrosine phosphorylation, followed by a reduction in IRS-1/PI3-kinase association in liver and muscle. The decrease observed in this study may be of biological importance because a reduction of receptor phosphorylation has been correlated with insulin resistance in different animal models (Saad et al, 1997). These results differed from those of Deutsch et al (1993) who reported no change in insulin receptor kinase activity in fructose-fed rats.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the effect of the menstrual cycle on this carbohydrate metabolism and insulin sensitivity remains to be determined. Clinical conditions such as pregnancy, where estrogen and progesterone concentrations are markedly raised, have a substantial effect on carbohydrate, lipid, and intermediary metabolism, as well as altering insulin sensitivity (Herrera et al 1991, Baaziz & Curry 1993, Metcalfe et al 1994, Saad et al 1997. Artificially raised levels of the sex steroid hormones, estrogen and progesterone, in women taking the combined oral contraceptive pill were found to affect glucose tolerance and insulin sensitivity (Godsland et al 1991, Watanabe et al 1994.…”
Section: Introductionmentioning
confidence: 99%